MENGGALI KETERLAKSANAAN KURIKULUM MERDEKA MELALUI MODEL EVALUASI CIPP: STUDI KASUS DI SDN 1 WONOCOYO SEBAGAI SEKOLAH MANDIRI BERUBAH - Lutfiani, Siwi; Laila, Alfi; Zunaidah, Farida Nurlaila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research is motivated by the Merdeka Curriculum policy as an innovative learning approach that impacts all education implementers, considering the numerous systemic changes from the previous curriculum. SDN 1 Wonocoyo has been identified as a school implementing the Merdeka Curriculum in the Independent Change category among 13 schools within a cluster in Panggul District, facing challenges in its implementation. The purpose of this study is to evaluate the Context, Input, Process, and Product aspects of the Merdeka Curriculum implementation at SDN 1 Wonocoyo. This research employs a mixed-methods approach using the CIPP evaluation model. The sample was determined purposively, consisting of 1 school principal and 9 class teachers. The research instruments included questionnaires, interview guidelines, observations, and documentation. Data analysis was conducted both quantitatively and qualitatively, then interpreted simultaneously. The results indicate that the implementation of the Merdeka Curriculum at SDN 1 Wonocoyo falls into the "Very Good" category, with details as follows: Context aspect 87.31%; Input 86.5%; Process 80.96%; and Product 89.68%. This evaluation result shows that the implementation of the Merdeka Curriculum at SDN 1 Wonocoyo has been successful across all aspects, making it a model for curriculum application at the elementary school level, particularly as an Independent Change School. Future research is recommended to explore the factors influencing the successful implementation of the Merdeka Curriculum in other schools.